The management of Pancreatic fistula Complicated by Gastric fistulation following Emergency Splenectomy - Tan Jih Huei; Henry Tan Chor Lip; Chow Sing Thou; Yuzaidi Mohamad; Rizal Imran Alwi (Journal of Trauma and Injury)
Pancreatic and gastric fistulas are rare complications of emergency splenectomy, and it is extremely rare for a pancreatic fistula to be further complicated by a fistulation into the stomach. Here, we present a case of pancreatogastric fistula in a 60-year-old man who experienced polytrauma due to a blunt mechanism. He underwent emergency splenectomy for splenic injury and developed a pancreatic fistula as a complication. A percutaneous endoscopic procedure was performed to drain the fistula, after which he developed a pancreatogastric fistula as a further complication. A double-pigtail stent was inserted via gastroscopy into the fistula tract to allow internal drainage of the pancreatic collection into the stomach cavity. When a pancreatic fistula is complicated by gastric fistulation, endoscopic stenting of the pancreatogastric fistula tract for internal drainage is an effective treatment option.